STATISTICAL, FINANCIAL AND INTERNAL REPORTING OF FOREST RESOURCES IN FORESTRY ENTERPRISES - SYSOIEVA, Inna; BARANENKO, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article offers a comprehensive analysis of the current state, content, and importance of statistical, financial, and internal reporting within Ukrainian forestry enterprises. It explores how these reporting systems support efficient forest resource management, ensure transparency in economic activities, and contribute to the sustainable development of the forestry sector in Ukraine.The study begins with a systematic overview of the existing approaches to compiling and presenting key reporting information. In doing so, it situates this evaluation within the broader context of global trends in forest management, including the increasing emphasis on digitalization, adherence to international best practices, and evolving environmental regulations. The research identifies a range of reporting components—such as timber production data, reforestation statistics, financial turnover figures, and internal management accounts—and assesses their role in driving operational efficiency and strategic planning.A central focus of the article is the examination of reforestation processes over recent years, particularly in light of the intensified policy measures and regulatory changes implemented in 2024. These elements are analyzed through the lens of both quantitative statistical outcomes and qualitative case-specific insights. Furthermore, the study highlights the significant strides made toward digitalizing accounting systems, including the integration of automated data collection, use of cloud-based platforms, and early adoption of e-reporting tools by leading forestry enterprises.Another key area of analysis involves the application of market indicators—such as timber prices, demand forecasts, and export/import statistics—and their representation in both financial and statistical reports. In conjunction with this, the article evaluates the impact of updated regulations introduced in 2024, including the alignment of Ukrainian standards with European Union directives on transparency, environmental responsibility, and corporate governance.Despite these advances, the article underscores several persistent challenges. These include fragmented data sources across different departments, insufficient levels of automation in internal reporting systems, low interoperability between databases, and slow adaptation to international sustainability reporting frameworks like IFRS and GRI. The authors argue that without addressing these issues, forestry enterprises may struggle to maintain competitiveness and credibility in both domestic and international markets.Ultimately, this study contributes to scholarly discourse by offering an in-depth evaluation of Ukrainian forestry enterprises’ reporting frameworks, pinpointing key obstacles, and charting a strategic path toward more efficient, transparent, and sustainable forest sector governance.
Keywords: forestry; statistical indicators; financial reporting; internal control; forest resources; digitalization; electronic wood accounting (EWA); sustainable development; environmental responsibility; regulatory policy